Bandage Lenses in the Postoperative Care for Cataract Surgery Patients: A Substitute for Eye Patch?. (15th May 2018) - Song, Hang; Li, Yingyu; Zhang, Yan; Shi, Danna; Li, Xuemin
Abstract : Purpose . To explore whether bandage lenses could be a safe and effective substitute for eye patch in the postoperative care for cataract surgery patients in terms of infection prevention, ocular impacts, and patient satisfaction. Methods . Patients who underwent cataract surgery were randomly divided into the eye patch group (Group A) and the bandage lens group (Group B). Bacterial culture samples were collected perioperatively from different sites. Evaluations of anterior segment condition and patient satisfaction were conducted on the first day of postoperative follow-up. Results . The positive rate of bacterial cultures in Group A was higher than that in Group B, but the difference was not statistically significant. Group B had significantly longer tear breakup time, higher tear meniscus height, and slightly better patient satisfaction than Group A. Conclusion . Bandage lenses can be used as a safe and effective substitute for eye patch in the postoperative care for cataract surgery patients. The Clinical Study registration number isChiCTR-IOC-17012167 .